Knowledge, willingness, uptake and barriers of cervical cancer screening services among Chinese adult females: a national cross-sectional survey based on a large e-commerce platform - Bo Zhang; Sumeng Wang; Xiyu Yang; Mingyang Chen; Wenhui Ren; Yanping Bao; Youlin Qiao (BMC, 2023)
Abstract Background Improving the coverage rate of cervical cancer screening is a challenge mission for cervical cancer elimination. This study attempted to assess the knowledge, willingness, and uptake of cervical cancer screening services among Chinese females and determined associated factors. Methods This is a cross-sectional online survey conducted in China from March to April 2022. Information on demographic characteristics, knowledge, willingness, and uptake of cervical cancer screening was collected through a large e-commerce platform. Women aged 18-65 were included in the analysis. Logistic regression analysis was employed to detect the possible factors associated with knowledge, willingness, and screening participation. Results A total of 4518 women (37.83 ± 9.14 years) were included in the final analysis, of whom 87.16% (n = 3938) lived in urban areas. About 93.40% (n = 4220) of the respondents reported hearing of cervical cancer screening. The median score of knowledge about cervical cancer was 16 out of 26. Over 84% (n = 3799) of the respondents were willing to receive regular cervical cancer screening. Nearly 40% (n = 1785) had never received cervical cancer screening. Among the screened women, 21.26% (n = 581), 35.24% (n = 1151), and 42.37% (n = 1158) were screened through a national cervical cancer screening program, employee physical examination, and self-paid physical examination, respectively. Knowledge was positively associated with willingness and screening participation. Age, marital status, occupation, monthly household income, and HPV vaccination history could influence screening participation (all p < 0.05). Conclusions Though women had high-level awareness and strong participation willingness in cervical cancer screening, the overall screening coverage among Chinese women was still low. Besides, the knowledge about cervical cancer was still limited. Comprehensive health education should be enhanced by utilizing social media platforms and medical workers. It is also important to promote national free cervical cancer screening with high-performance screening methods.